Analysis of the Decision System for Selecting Interest in Concentration Using the SMART Method - Wahyu Nur Alimyaningtias; Isa Rosita; Djumhadi; Novi Indrayani (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
The information technology study program at the Faculty of Computer Science, Mulia University has two areas of concentration, namely network technology and forensic and security architecture. Students tend to be confused in determining their interest in one of the concentrations so that they are less prepared in choosing concentration courses that suit their talents and interests. This research aims to make it easier for students to classify the types of interests according to their interests. Especially 5 & 6 semester students who are involved in the Information Technology (IT) study program. IT students, have tendencies such as confusion, or doubts in choosing a concentration interest in the study program. Therefore, by conducting this research and realizing its objectives, data collection and data analysis techniques were used and SMART Decision Analysis (Simple Multi Attribute Rating Techniue) was used to produce decisions for students who had the interests and talents of the selected concentrations